Studi Prilaku Konsumen Dimasa Pandemi Covid-19: Keputusan Pembelian Smartphone Berbasis Android Dalam Perspektif Citra Merek Dan Kepuasan Konsumen - Usman Effendi; Yantri Rumnita (Kodepena Indonesia, 2020)
Purpose: The rapid use of Android smartphones among students is an impetus to find out how much influence brand image and consumer satisfaction have on purchasing decisions for Android-based smartphones and the influence of brand image and consumer satisfaction on purchasing decisions for Android-based smartphones during the Covid-19 pandemic. Most of the students conducted online lectures during the Covid-19 pandemic, Android smartphones were an alternative choice of practical tools to access online lectures during the Covid-19 pandemic. The research method used is quantitative method with brand image and customer satisfaction independent variables and the dependent variable is the purchase decision. The population in this research is an unlimited number of students in Jakarta. Furthermore, the sampling technique used incidental sampling with a sample size that met the criteria as many as 132 participants. The data collection technique used a questionnaire with a Likert scale model on a scale of brand image, customer satisfaction and purchase decisions. The results of the analysis found that there is a partial and significant effect of brand image on purchasing decisions for Android smartphones. There is a partial and significant effect of consumer satisfaction on purchasing decisions for Android smartphones. And there is a joint influence on brand image and customer satisfaction on purchasing decisions. So that the results of this study can state that the better the brand image and the increase in customer satisfaction, it will also increase the decision to buy an android smartphone among students.